Synaptotagmin VII Restricts Fusion Pore Expansion during Lysosomal Exocytosis - Jaiswal, Jyoti K; Chakrabarti, Sabyasachi; Andrews, Norma W; Simon, Sanford M (PLOS Biology, 2004)
Lysosomes only partially release their contents in wild-type mouse embryonic fibroblasts (MEFs); but in MEFs in which synaptotagmin VII has been deleted, lysosomes fuse completely.